2017
DOI: 10.5194/acp-17-5623-2017
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of aerosol effects on warm clouds over the Yangtze River Delta from multi-sensor satellite observations

Abstract: Abstract. Aerosol effects on low warm clouds over the Yangtze River Delta (YRD, eastern China) are examined using co-located MODIS, CALIOP and CloudSat observations. By taking the vertical locations of aerosol and cloud layers into account, we use simultaneously observed aerosol and cloud data to investigate relationships between cloud properties and the amount of aerosol particles (using aerosol optical depth, AOD, as a proxy). Also, we investigate the impact of aerosol types on the variation of cloud propert… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
47
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 84 publications
7
47
2
Order By: Relevance
“…The computed slopes from linear regressions of CER versus AI on log‐log scale with LWP‐stratified for the layer 650–950 hPa over three anthropogenic regions and their adjacent oceans are summarized in Figure , which clearly show that for a given LWP, slopes are normally negative over ocean but positive over land. The opposite correlation over land has been reported, though not explained, in a few previous studies (Grandey & Stier, ; Liu et al, ; Tang et al, ; Wang et al, , ; Yuan et al, ). It is interesting to see that as LWP increases, the positive slopes over land become weaker while negative slopes over ocean change slightly.…”
Section: Aerosol‐cloud Correlationsmentioning
confidence: 63%
See 1 more Smart Citation
“…The computed slopes from linear regressions of CER versus AI on log‐log scale with LWP‐stratified for the layer 650–950 hPa over three anthropogenic regions and their adjacent oceans are summarized in Figure , which clearly show that for a given LWP, slopes are normally negative over ocean but positive over land. The opposite correlation over land has been reported, though not explained, in a few previous studies (Grandey & Stier, ; Liu et al, ; Tang et al, ; Wang et al, , ; Yuan et al, ). It is interesting to see that as LWP increases, the positive slopes over land become weaker while negative slopes over ocean change slightly.…”
Section: Aerosol‐cloud Correlationsmentioning
confidence: 63%
“…In recent years, however, quite a few studies found that this relation is not always true; instead, the negative correlation between aerosol particles and CER is not found distinctly or could be even positive; that is, CER increases with aerosol number (Bulgin et al, 2008;Grandey & Stier, 2010;Liu et al, 2017;Sekiguchi et al, 2003;Tang et al, 2014;Wang et al, 2014Wang et al, , 2015Yuan et al, 2008). It is acknowledged that aerosol-cloud interactions are quite complex processes, influenced by both aerosol microphysics ( composition) and meteorological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, not all aerosols on the vertical column are actually involved in cloud formation, thus this 130 assumption is relatively rough. Several studies revealed that aerosols have little effect on cloud properties when aerosol and cloud layers are clearly separated Bré on, 2010, 2013;Liu et al, 2017). In this study, the impact of CCN number concentration near cloud layer, e.g.…”
Section: Relationships Between Aerosol and Cloud Propertiesmentioning
confidence: 63%
“…The analysis of aerosol-cloud interactions has been reported in literature by a variety of methods: studies presenting results from global scales (Feingold et al, 2001;Quaas et al, 2010) to regional scales (e.g. Saponaro et al, 2017;Ban-Weiss et al, 2014;Liu et al, 2017Liu et al, , 2018 and in situ observations (e.g. Sporre et al, 2014), using different approaches, i.e.…”
Section: Introductionmentioning
confidence: 99%